An Analysis of the Performance of the Comprehensive Tax Plan in Iran (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As it is known, the tax received by the governments from real and legal persons is one of the main sources of income that is used by governments in the management of country and providing their current costs. The developed countries compared to developing states enjoy the more robust and sophisticated mechanisms in tax collection. Iran is not an exception too and all tax collection processes are integrated in a plan known as “comprehensive tax plan”. In this article, we investigate the advantages and disadvantages of this plan for Iranian economy considering the goals claimed by those involved in designing this plan; on the other hand, we try to provide a new and more robust prospect for the authorities of the Ministry of Economic Affairs and Finance by including actual and numerous samples in this study. Given that the ultimate foal of Iranian comprehensive tax plan is eliminating excessive and unnecessary investigations and correspondence for state and non-state organizations in identifying the income and activities of tax payers, the disadvantages of this plan are identified in this study, so that alternative solutions could be replaced. At the end, the unanimous answer to our question concerning the comprehensive tax plan implementation in Iran is that this plan is a pilot one and it has a long way ahead to be developed to its desired form. In response, this question should be posed that whether the current economic conditions prevailing Iranian markets sustains different experiments and tests of the authorities of this plan?.